Temporal Registration of Cardiac Multimodal Images Using Locally Linear Embedding Algorithm - Talayeh Ghodsizad; Hamid Behnam; Emad Fatemizadeh; Taraneh Faghihi Langroudi; Fariba Bayat (Frontiers in Biomedical Technologies, 2021)
Purpose: Multimodal Cardiac Image (MCI) registration is one of the evolving fields in the diagnostic methods of Cardiovascular Diseases (CVDs). Since the heart has nonlinear and dynamic behavior, Temporal Registration (TR) is the fundamental step for the spatial registration and fusion of MCIs to integrate the heart's anatomical and functional information into a single and more informative display. Therefore, in this study, a TR framework is proposed to align MCIs in the same cardiac phase.